Microbiological testing of devices used in maintaining peripheral venous catheters - Fernanda de Paula Rossini; Denise de Andrade; Lissandra Chaves de Sousa Santos; Adriano Menis Ferreira; Caroline Tieppo; Evandro Watanabe
ABSTRACT Objective: to evaluate the use of peripheral venous catheters based on microbiological analysis of devices (dressing and three-way stopcocks) and thus contribute to the prevention and infection control. Methods: this was a prospective study of microbiological analysis of 30 three-way stopcocks (external surfaces and lumens) and 30 dressing used in maintaining the peripheral venous catheters of hospitalized adult patients. Results: all external surfaces, 40% of lumens, and 86.7% of dressing presented bacterial growth. The main species isolated in the lumen were 50% coagulase-negative Staphylococcus, 14.3% Staphylococcus aureus, and 14.3% Pseudomonas aeruginosa. Fifty nine percent of multidrug-resistant bacteria were isolated of the three-way stopcocks, 42% of the lumens, and 44% of the dressing with a predominance of coagulase-negative Staphylococcus resistant to methicillin. Besides, 18% gram-negative bacteria with resistance to carbapenems were identified from multidrug-resistant bacteria on the external surfaces of the three-way stopcocks. Conclusion: it is important to emphasize the isolation of coagulase-negative Staphylococcus and gram-negative bacteria resistant to methicillin and carbapenems in samples of devices, respectively, which reinforces the importance of nursing care in the maintenance of the biologically safe environment as well as prevention and infection control practices.